2018
DOI: 10.1111/eos.12582
|View full text |Cite
|
Sign up to set email alerts
|

Head positioning in a cone beam computed tomography unit and the effect on accuracy of the three‐dimensional surface mode

Abstract: Head position during cone beam computed tomography (CBCT) examination can easily deviate from the ideal, which may affect the accuracy of the segmented three‐dimensional (3D) model. The aim of this study was to determine the effect of head positioning on the accuracy of the 3D model. A human dry skull was positioned at predetermined orientations in a CBCT scanner and scanned in multiple orientations and voxel sizes. The resulting 3D surface models were superimposed over those derived from the reproducible cent… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 11 publications
(5 citation statements)
references
References 42 publications
0
3
0
Order By: Relevance
“…In a similar study with a dry skull and variation of the position of the head, Sabban et al suggested that the head position might significantly influence linear measurements in CBCT scans, especially vertical and horizontal measurements as a result of extension and flexion head movements [22]. Another study in dry skulls showed that different head positions and orientations affected 3D model segmentation, but these differences were not clinically relevant [23]. In studies with dry skulls, the images are, however, not similar to clinical images as soft tissue is absent; it might be that clinical images would have more significant differences.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In a similar study with a dry skull and variation of the position of the head, Sabban et al suggested that the head position might significantly influence linear measurements in CBCT scans, especially vertical and horizontal measurements as a result of extension and flexion head movements [22]. Another study in dry skulls showed that different head positions and orientations affected 3D model segmentation, but these differences were not clinically relevant [23]. In studies with dry skulls, the images are, however, not similar to clinical images as soft tissue is absent; it might be that clinical images would have more significant differences.…”
Section: Discussionmentioning
confidence: 99%
“…Different orientations of CBCT images might influence the operator's ability to identify landmarks and perform measurements, affecting the vertical measurements [22]. The orientation of the scan also affects 3D model segmentation [23]. Therefore, it is essential to virtually orient the CBCT images in order to improve the reliability in landmark detection, measurements, and segmentation.…”
Section: Introductionmentioning
confidence: 99%
“…However, the study designs are either arbitrary with fiducial markers or based on dry skull models 5,15,16 . Although lately different methods for head orientation in 3D space have been proposed, they have either been focused on 3D facial scans or based on high-resolution medical CT images 4,[17][18][19][20] .…”
Section: Reorientation Methodology For Reproducible Head Posture In S...mentioning
confidence: 99%
“…The use of scanned X-rays from exposed film and their digital processing does not cause any changes in the skeletal reference points on cephalograms that limit their diagnostic evaluation (54). However, any scientific analysis of X-rays requires information on the measurement accuracy of the study (55)(56)(57)(58). Identifying landmarks is a critical step in cephalometric analysis and is prone to error.…”
Section: Alternative Referencing For Horizontal Plane: Sphenoid Bonesmentioning
confidence: 99%
“…However, the problem of measurement accuracy and error analysis must be considered in every study, regardless of the radiological imaging technology (64). For example, positioning errors may occur both with X-ray techniques that are based on threedimensional recording of the object (55,56,58); this is wellknown in standard cephalometry (64). Nevertheless, twodimensional cephalometry is still a standard tool in orthodontic and maxillofacial surgery treatment planning, for which the skull assessment in the lateral cephalogram is essential (63).…”
Section: Alternative Referencing For Horizontal Plane: Sphenoid Bonesmentioning
confidence: 99%